When Music Takes Over in Film - Anna K. Windisch; Tieber, Claus; Powrie, Phil (2023)
This open access collection deals with musical moments in film as one of the most pivotal and compelling issues of current film music research. Musical moments as defined by Amy Herzog occur when a musical number inverts the normal relationship between the image track and the soundtrack in a film in such a way that what we see is determined by what we hear. As one potential approach, this definition provokes a variety of perspectives to investigate the disruptive potential of these moments and numbers as a creative device in the production of audiovisual narratives.